Multi-scenario simulation and eco-environmental effect analysis of “Production–Living–Ecological space” based on PLUS model: A case study of Anyang City - Li Lei; Li Genming; Ji Guangxing; Li Qingsong; Zhang Zhihao; Chen Weiqiang (Open Geosciences)
By simulating the layout of the “Production–Living–Ecological space” under various scenarios in the future and exploring the trend of future land use changes, it is of great significance to optimize the land use structure and ecological environment of the region. Based on the existing land use data and combined with the PLUS model, the article predicts the land demand and distribution of the PLES in the future 2040 and 2060 and then studies the contribution rate of the area changes of each land type to the change of regional ecological environment quality. The results show that (1) agricultural production land is the main type of land use in Anyang City from 1980 to 2020, and the conversion type of land use is mainly manifested as the conversion of agricultural production land to living land. (2) In all three scenarios, the main changes between 2020 and 2060 are the contraction of production land and the expansion of living land. The change rate of the ecological protection scenario is the smallest, and the decrease rate of the urban development scenario is the largest. (3) In 2060, all three scenarios show varying degrees of reduction in the Ecological environment quality index (EQI) compared to 2020. At the same time, the change in regional environmental quality is closely related to the change in agricultural land. (4) The regional ecological environment quality is the result of multi-factors, among which annual precipitation has the strongest explanatory power, and all factors show synergistic effects. The present study is intended to provide a reference for optimizing the pattern of the PLES in the region and improving the regional environmental quality.